Effects of Serum Calcium and Phosphorus under Different Feeding Conditions on Production Traits of Young Xinjiang Brown Bulls - Abuduwaili, Julaiti; Ren, Wanping; Zhang, Hao; Lv, Qiang; Yu, Xiong (Hunan agricultural science & technology newsletter : HASTN, 2014)
In the Xinjiang new era from October 2012 to February 2013, an agricultural and animal husbandry Co Ltd feedlot Yining Tuogelake village used tethered and scattered feeding methods to conduct fattening young Xinjiang brown cattle experiment. The 16-month-old young Xinjiang brown bulls were selected totaling 68 heads, divided into scattered group and tethered group. Male claves were taken as test subjects from October to February of following year and body conformation linear evaluation were made, followed by measurement of body size indexes and Regular collection of Blood samples. Scattered feeding can significantly improve the young Xinjiang brown cattle's daily gain, accelerate the body height, heart girth, body length, and body growth. What's more, scattered feeding serum calcium and phosphorus content are significantly higher than tethered feeding.